The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1536/jhj.45.789
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Training After Open Heart Surgery on Quality of Life and Exercise Tolerance in Patients With Mitral Regurgitation or Aortic Regurgitation

Abstract: We conducted a questionnaire survey regarding quality of life (QOL) to evaluate the effects of exercise training on the QOL in patients with valvular heart disease after surgery. This study included 64 consecutive patients who underwent heart surgery. They were divided into two groups: exercise training could (EX(+) group, n = 31) and could not be performed (EX(-) group, n = 33) until 6 months after surgery. To evaluate the QOL and exercise tolerance, we employed "a questionnaire regarding disease and quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 10 publications
2
20
1
5
Order By: Relevance
“…In the late postoperative period after cardiac surgery, carrying out exercises in patients with valve disease can improve their tolerance of exercise, as well as their quality of life, although there are no significant alterations in lung function [27]. Table 1 shows some respiratory complications resulting from surgery and some suggestions for possible physiotherapeutic interventions evaluated in some studies.…”
Section: Physiotherapeutic Approach After Extubationmentioning
confidence: 99%
“…In the late postoperative period after cardiac surgery, carrying out exercises in patients with valve disease can improve their tolerance of exercise, as well as their quality of life, although there are no significant alterations in lung function [27]. Table 1 shows some respiratory complications resulting from surgery and some suggestions for possible physiotherapeutic interventions evaluated in some studies.…”
Section: Physiotherapeutic Approach After Extubationmentioning
confidence: 99%
“…Close surveillance of patients during their physical training is essential (14). Earlier studies have shown that after a six-month physical training in patients after heart valve surgery their quality of life was significantly improved (15). A study was conducted to examine the effect of a twelve-week aerobic dynamic physical exercise on heart muscle remodeling in patients after corrective TOF surgery, which demonstrated that there were no harmful effects of physical training on cardiac remodeling (14).…”
Section: Discussionmentioning
confidence: 99%
“…Sie zeigen eine ähnliche Verbesserung der körperlichen Leistungsfähigkeit wie bei KHK-Patienten [102][103][104][105][106][107][108][109][110][111].…”
Section: Evidenzunclassified
“…Trainingsprogramme über 1-12 Monate mit 3-7 Trainingseinheiten pro Woche hatten einen positiven Effekt in Bezug auf die Belastbarkeit bei Patienten nach Aortenklappenersatz, nach Mitralklappenvalvuloplastie und nach Mitralklappenersatz [102,[104][105][106][107][108][109][110][111][112].…”
Section: Evidenzunclassified